The Impact Methicillin-Resistant Staphylococcus aureus (MRSA) and Vancomycin-Resistant Enterococcus (VRE) Flags on Hospital Operations - Shenoy, Erica S. (Infect Control Hosp Epidemiol, 2016)
OBJECTIVE: To determine the impact of MRSA/VRE designations, or flags, on selected hospital operational outcomes. DESIGN: Retrospective cohort study of inpatients admitted to the Massachusetts General Hospital during 2010–2011. METHODS: Operational outcomes were time to bed arrival, acuity-unrelated within-hospital transfers, and length of stay. Demographic and clinical characteristics – including age, gender, severity of illness on admission, admit day of week, residence prior to admission, hospitalization within the prior 30 days, clinical service, and discharge destination – were used as covariates. RESULTS: A total of 81,288 admissions were included. After adjusting for covariates, patients with a MRSA/VRE flag at the time of admission experienced a mean delay in time to bed arrival of 1.03 (9.63 [95% CI 9.39–9.88] hours vs. 8.60 [95% CI 8.47–8.73] hours); had 1.19 times the odds [95% CI, 1.13–1.26] of experiencing an acuity-unrelated within-hospital transfer, and experienced a mean length of stay 1.76 days longer (7.03 [95% CI 6.82–7.24] days vs. 5.27 [95% CI 5.15–5.38] days) compared to patients with no MRSA/VRE flag. CONCLUSIONS: MRSA/VRE designation was associated with delays in time to bed arrival, increased likelihood of acuity-unrelated within-hospital transfers, and extended length of stay. Efforts to identify patients who have cleared MRSA/VRE colonization are critically important to mitigate inefficient use of resources and improve inpatient flow.